Patient-derived podocyte spheroids reveal new insights into the etiopathogenesis of Alport syndrome - Romero-Guevara, Ricardo; Nicolaou, Orthodoxia; Petracca, Benedetta; Shaheed, Sadr; Sutton, Christopher; Frangou, Eleni; Afami, Marina; Kyriacou, Kyriacos; Ioannides, Adonis; Xinaris, Christodoulos (Frontiers in Cell and Developmental Biology, 2023)
Alport syndrome (AS) is a rare disease characterized by defective glomerular basement membranes, caused by mutations in COL4A3, COL4A4, and COL4A5, which synthesize collagen type IV. Patients present with progressive proteinuria, hematuria and podocyte loss. There is currently no cure for Alport syndrome, and this is mainly due to its complex and variable pathogenesis, as well as the lack of models that can faithfully mimic the human phenotype. Here we have developed a novel human culture model of Alport syndrome and used it to study the effects of different mutations on podocyte development and biology. First, we established a differentiation protocol that allowed us to generate podocyte spheroids from patient-derived human induced pluripotent stem cells (hiPSCs). We have then carried out discovery proteomics and demonstrated that a total of 178 proteins were differentially expressed between Alport (AS1 and AS3) and control (LT) podocytes. GO analysis indicated alterations in several metabolic pathways, such as oxidative phosphorylation, RNA maturation, chromatin condensation, and proliferation. Although functional assays showed no changes in lactate production and mitochondrial potential compared to healthy controls, immunofluorescence and electron microscopy analysis showed key morphological changes related to the phenotypical maturation of Alport podocytes. Moreover, the studied mutations led to persistent proliferation, increased reactive oxygen species (ROS) production and the concomitant expression of peroxisome proliferator-activated receptors α and γ (PPARα and PPARγ) in podocytes. These data on patient-derived podocytes provide evidence that collagen mutations, in addition to playing a central role in the defective development of the glomerular filtration barrier, cause significant alterations in podocyte development and metabolism very early in development, even before the formation of the filtering apparatus. In conclusion, our study provides a new methodological platform for the differentiation of podocytes and to study human podocytopathies in a personalized manner, and reveals new insights into the etiopathogenesis and pathobiology of Alport syndrome.